PENGELOLAAN ROYALTI LAGU DAN MUSIK PADA PLATFORM DIGITAL - Nizar Fikri; Elfrida Ratnawati Gultom (Ensiklopedia of Journal, 2023)
Copyright in addition to having moral rights to its creators also has economic rights in the form of royalty. The rules of implementation of the Law Number 28 of 2014 on the Copyright are the Government Regulations No. 56 Year 2021 On the Management of Copyright of Songs and/or Music. The purpose of  this Government Regulation is to provide protection and legal certainty to the creators and to optimize the management function of royalty in accordance with the provisions of Articles 87, Articles 89 and 90 of the Copyright Act, it is necessary to from a system of management system of the copyright royalties of songs and/or music implemented by the Collective Management Institute (LMK) and the National Collegiate Management Institute. (LMKN). The purpose of LMKN is to become a one-door royalty management service. This paper analyzes the authority and tasks of LMK and LMKN in managing the royalties of music or songs used on digital platforms such as streaming apps. From the results of the research, it was concluded that there are two different agencies with different authority in the management of royalties, namely LMK and LMKN. One of the differences is that the LMKN has the authority to regulate and set values that will have a difference with the LMK so as to give more legal certainty about the duties and authority of the LMK and the LNKN.Keywords: Copyright, Authority, LMK, LMKN, Royalty, Digital Platform.